Ozonizers For Agricultural Problems and Their Use in Pre-Sowing Treatment of Cotton and Other Crops (Texas Journal of Multidisciplinary Studies, 2022)
The article presents the results of studies of the effect of ozone treatment on the sowing qualities of seeds, including cotton. The parameters of the developed corona discharge ozonator with a capacity of up to 10-12 g/h, used for pre-sowing treatment of seeds and solutions, are given. The sowing qualities of seeds were studied depending on the modes of ozone treatment and the optimal effects of ozone were established at a dose of about 22-30 g/ton. A noticeable decrease in the microbial contamination of seeds and the expediency of using pre-sowing ozone treatment are shown.